Open science practices in traditional, complementary, and integrative medicine research: A path to enhanced transparency and collaboration - Jeremy Y. Ng; L. Susan Wieland; Myeong Soo Lee; Jian-ping Liu; Claudia M. Witt; David Moher; Holger Cramer (Integrative Medicine Research)
This educational article explores the convergence of open science practices and traditional, complementary, and integrative medicine (TCIM), shedding light on the potential benefits and challenges of open science for the development, dissemination, and implementation of evidence-based TCIM. We emphasize the transformative shift in medical science towards open and collaborative practices, highlighting the limited application of open science in TCIM research despite its growing acceptance among patients. We define open science practices and discuss those that are applicable to TCIM, including: study registration; reporting guidelines; data, code and material sharing; preprinting; publishing open access; and reproducibility/replication studies. We explore the benefits of open science in TCIM, spanning improved research quality, increased public trust, accelerated innovation, and enhanced evidence-based decision-making. We also acknowledge challenges such as data privacy concerns, limited resources, and resistance to cultural change. We propose strategies to overcome these challenges, including ethical guidelines, education programs, funding advocacy, interdisciplinary dialogue, and patient engagement. Looking to the future, we envision the maturation of open science in TCIM, the development of TCIM-specific guidelines for open science practices, advancements in data sharing platforms, the integration of open data and artificial intelligence in TCIM research, and changes in the context of policy and regulation. We foresee a future where open science in TCIM leads to a better evidence base, informed decision-making, interdisciplinary collaboration, and transformative impacts on healthcare and research methodologies, highlighting the promising synergy between open science and TCIM for holistic, evidence-based healthcare solutions.